Effect of microstructure and grain boundary chemistry on slow crack growth in silicon carbide at ambient conditions. Issue 8 (August 2015) - Al Nasiri, N.; Ni, N.; Saiz, E.; Chevalier, J.; Giuliani, F.; Vandeperre, L.J.
Abstract Silicon carbide (SiC) is being used increasingly as a room temperature structural material in environments where moisture cannot always be excluded. Unfortunately, there have been almost no reports on slow crack growth (SCG) in SiC at room temperature. To address this gap, SCG in SiC was studied using constant stress rate and double torsion tests in water. SiC based materials were produced with a wide range of grain boundary chemistries and microstructures, which may affect their slow crack growth behaviour. To clarify the role of chemistry and microstructure respectively, solid state (SS) sintering with carbon and boron along with liquid phase (LP) sintering using oxides additives were used to produce materials with fine and coarse grains. The LP-SiC was three times more sensitive to SCG than SS-SiC materials. Moreover, the larger grained material with a higher toughness was less sensitive to SCG than the materials with fine grains.